2017
DOI: 10.1001/jamaneurol.2016.5042
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Treated Depression With Epilepsy and Seizure Outcomes

Abstract: IMPORTANCE A bidirectional relationship exists between epilepsy and depression. However, any putative biological gradient between depression severity and the risk of epilepsy, and the degree to which depression mediates the influence of independent risk factors for epilepsy, has yet to be examined.OBJECTIVE To determine the effect of depression on the risk of epilepsy and seizure outcomes. DESIGN, SETTING, AND PARTICIPANTSAn observational study of a population-based primary care cohort (all patients free of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 25 publications
6
110
0
Order By: Relevance
“…In our cohort, the odds ratio of pharmacoresistance with co‐occurrence of anxiety and depressive symptoms was 7.7, in accordance with a recent report of an odds ratio of 6.1 for refractoriness when patients presented a psychiatric disorder (including depression, anxiety, and schizophrenia) . These results are consistent with our recent temporal lobe epilepsy analyses, as the odds ratio of pharmacoresistance with concurrent anxiety and mood disorders was 4.4, reinforcing the hypothesis of common neurobiological mechanisms between epilepsy and psychiatric disorders . Although the natural idea is that pharmacoresistant seizures cause anxiety and depression, both animal models and population‐based studies have provided evidence of a more bidirectional relationship between psychiatric disorders and epilepsy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cohort, the odds ratio of pharmacoresistance with co‐occurrence of anxiety and depressive symptoms was 7.7, in accordance with a recent report of an odds ratio of 6.1 for refractoriness when patients presented a psychiatric disorder (including depression, anxiety, and schizophrenia) . These results are consistent with our recent temporal lobe epilepsy analyses, as the odds ratio of pharmacoresistance with concurrent anxiety and mood disorders was 4.4, reinforcing the hypothesis of common neurobiological mechanisms between epilepsy and psychiatric disorders . Although the natural idea is that pharmacoresistant seizures cause anxiety and depression, both animal models and population‐based studies have provided evidence of a more bidirectional relationship between psychiatric disorders and epilepsy.…”
Section: Discussionsupporting
confidence: 92%
“…The impact of the combined symptoms of anxiety and depression on patients’ lives cannot be disregarded, as they may experience stress and sleep problems that can directly influence seizure frequency . A recent population‐based study demonstrated that depression (and treated depression) was associated with poor seizure control, suggesting that “severity of depression is associated with severity of epilepsy.” The complex interaction between epilepsy and psychiatric disorders deserves further investigation and underscores the importance of treating both conditions to improve seizure control and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…An editorial in the same issue of the journal in which the study was published cautioned the readers on the conclusions reached by the Taiwanese investigators, as they had failed to factor‐in the role of the depressive disorder for which the SSRIs were prescribed in the higher risk of epilepsy . In fact, the increased risk of epilepsy identified in this study was comparable to a 2.5 higher risk reported in 2 population‐based studies from the United Kingdom cited earlier …”
Section: Complex Relation Between Common Psychiatric Comorbidities Anmentioning
confidence: 46%
“…Several population‐based studies have suggested that primary depression increases the risk of developing epilepsy by twofold and suicidality by three‐ to fourfold, and as indicated above, a mood disorder preceding the onset of epilepsy has been associated with an increased risk of developing treatment‐resistant epilepsy . It follows from these observations that treatment of PCs should be followed by an improved seizure outcome and better tolerance of antiepileptic drugs (AEDs).…”
Section: Complex Relation Between Common Psychiatric Comorbidities Anmentioning
confidence: 97%
See 1 more Smart Citation